Introducing Algorithmic Thinking in Primary Education in Greece - Karakostas, Athanasios; Liarokapis, Vasilis; Vlachou, Akrivi (2022 7th South-East Europe Design Automation, Computer Engineering, Computer Networks and Social Media Conference (SEEDA-CECNSM), 2022)
This paper aims to address the issue of lack of teaching of algorithmic thinking to primary school students in the Greek education system. In our research, we focus on primary school students and introduce material and lesson plans that can be used by teachers who may not have any knowledge of computer science and without the usage of a computer. We show that it is possible for students to comprehend and use algorithms in the context of every day tasks, but also in the context of other subjects (most notably Mathematics). We conducted an in-class evaluation of the proposed approaches using a group of student who had no previous contact with the subject of algorithms or programming. Our results shows that our approach managed to attract the interest of the majority of the students, while many of them were interested in learning even more about algorithms and computer science in the future.